2021
DOI: 10.3389/fmicb.2021.779369
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Insights Into Community Interactions, Assembly Processes and Function in the Denitrifying Phosphorus Removal Activated Sludge Driven by Phosphorus Sources

Abstract: The microbial characteristics in the wastewater treatment plants (WWTPs) strongly affect their optimal performance and functional stability. However, a cognitive gap remains regarding the characteristics of the microbial community driven by phosphorus sources, especially co-occurrence patterns and community assembly based on phylogenetic group. In this study, 59 denitrifying phosphorus removal (DPR) activated sludge samples were cultivated with phosphorus sources. The results suggested that homogeneous selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, for the pure effect, we found that the Pi fractions had a higher explanation than Po fractions for bacterial beta diversity ( Figure 6 ). As an essential component of nucleic acids, lipids or storage energy molecules, Pi can substantially influence the shaping of microbial community structure and ecological patterns or processes ( Zheng et al, 2021 ). As such, this finding largely stresses the importance of Pi in shaping bacterial community structures, which is concordant with previous findings on aquatic bacteria ( Yuan et al, 2022 ) or phytoplankton ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, for the pure effect, we found that the Pi fractions had a higher explanation than Po fractions for bacterial beta diversity ( Figure 6 ). As an essential component of nucleic acids, lipids or storage energy molecules, Pi can substantially influence the shaping of microbial community structure and ecological patterns or processes ( Zheng et al, 2021 ). As such, this finding largely stresses the importance of Pi in shaping bacterial community structures, which is concordant with previous findings on aquatic bacteria ( Yuan et al, 2022 ) or phytoplankton ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, such major role of deterministic processes has also been observed in soils ( Moroenyane et al, 2016 ) and rivers ( Vilmi et al, 2020 ). Similarly, phosphorus fractions contain large amounts of organic or inorganic P, providing essential nutrients for microbial growth ( Zheng et al, 2021 ). Such nutrients can alter even biodiversity and its relationship with temperature in large-scale field experiments ( Wang et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided theories, niche-based theory and neutral theory, for microorganism gathering (i.e., assembly) [10]. Traditional niche-based theories hypothesize that community selection is constrained by environmental conditions, species characteristics, and interspecies interactions [11,12]. In contrast, neutral theory assumes that community structures are independent of species traits and governed by drift, dispersal, random speciation, death, and extinction [13].…”
Section: Introductionmentioning
confidence: 99%